Pengaruh Pendidikan Kesehatan Masyarakat Terhadap Pengetahuan Tentang Penanganan Demam Berdarah Dengue - Mei Lestari I.W; Hasiratul Khudsiyah (Indonesian Health Science Journal, 2021)
Introduction: Health education is a number of influential experience in profitable against habits, attitudes, and knowledge related to the health of individuals, communities, and Nations. Health education about knowledge of Dengue Hemoragic Fever (DHF) is an important and urgent things to do. Methods: This research uses experimental design pre test and post pre-loaded test one group design. This population is the community at RT. 7 RW. 01 Wards of coral in the Sub District of Sampang District of Sampang as much as 277 people. Purposive sampling technique used with sampling total sample 120 heads of Families or representing. How data retrieval using a questionnaire type closed-ended question dichotomy. Result: The results of the study before a given health education obtained the majority (51%) less and after given health education the majority (56%) either. Based on the results of the statistical tests using SPSS test Wiloxon Sign Ranks test obtained P = 0.000 with α = 0.05 <. Conclusions: Knowledge about the handling of the dengue fever Dengue DBD is already good but should be further enhanced to be aware in order that HE MIGHT not too many sufferers and could prevent it with the knowledge already acquired from the granting of health education about Dengue Hemoragic Fever (DHF).